Dukungan Sosial dan Adversity Quotient pada Remaja yang Mengalami Transisi Sekolah - Dian A. Puspasari; Toto Kuwato; Hariz E. Wijaya (Fakultas Psikologi dan Ilmu Sosial Budaya Universitas Islam Indonesia Yogyakarta, 2012)
The aim of this study was to understand the relationship between social support and adversity quotient in adolescent school transition. The hypothesis of this study was “there was a relationship between social support and adversity quotient in adolescent school transition”. Subjects in this study are 7th grade students in Sleman. All subjects are female and about 11 to 14 years old. This study used Social Supports Scale & Adversity Quotient Scale made by researchers. The Social Support Scale refer to House's theory and the adversity quotient refer to Stoltz's theory. This study use Pearson's Product Moment Correlation to examine whether there was a correlation between social support and adversity quotient in adolescent school transition. Data analysis showed r= 0.520, p = 0.000 (p<0.01) which mean that there was a very significant positive correlation between social support and adversity quotient. From the result of the study, we can conclude that social support has impact on adversity quotient in adolescent school transition.Keywords: adversity quotient, social support, school transition